2018
DOI: 10.18551/rjoas.2018-04.03
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Leadership on Organizational Citizenship Behaviour Through Work Climate and Job Satisfaction

Abstract: The success and failure of the system in educational institutions depend on leaders. Leaders who are able to nurture the teachers, who become subordinates, will certainly improve the work atmosphere. The purpose of this study is to examine and analyze the effect of leadership on job satisfaction and work climate oriented on the organizational citizenship behavior. This study adopted quantitative research, with sampling technique used is probability cluster sampling with 78 respondents selected at some Madrasah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…This proved that job satisfaction has a positive effect on OCB (Zeinabadi, 2010), signified by contentment with the earnings, positive responses to work results by the leadership, and increased collaboration with colleagues. This was in line with Dewi & Sudibya (2016), Tistianingtyas & Parwoto (2021), Fauzi (2021), Apridar & Adamy (2018), Fitrio, Apriansyah, Utami, & Yaspita (2019, Herminingsih & Kasuri (2018), Sahyoni & Supartha (2020), Agus & Suparman Lalu (2015), and Rahman (2014), which found that job satisfaction positively influences OCB.…”
Section: Path Analysis Resultssupporting
confidence: 80%
“…This proved that job satisfaction has a positive effect on OCB (Zeinabadi, 2010), signified by contentment with the earnings, positive responses to work results by the leadership, and increased collaboration with colleagues. This was in line with Dewi & Sudibya (2016), Tistianingtyas & Parwoto (2021), Fauzi (2021), Apridar & Adamy (2018), Fitrio, Apriansyah, Utami, & Yaspita (2019, Herminingsih & Kasuri (2018), Sahyoni & Supartha (2020), Agus & Suparman Lalu (2015), and Rahman (2014), which found that job satisfaction positively influences OCB.…”
Section: Path Analysis Resultssupporting
confidence: 80%
“…However the study was conducted in a context of learning institution limiting the generalization of the findings to the health sector. Agus and Lalu (2018) analyzed the effect of leadership on job satisfaction and work climate oriented on the organizational citizenship behavior. This study adopted quantitative research, with sampling technique used is probability cluster sampling with 78 respondents selected at some Madrasah Aliyah Negeri (Senior High School) in Lombok.…”
Section: Objectives Of the Studymentioning
confidence: 99%